Obesity and labor market in Peru - Nuñez, Roy (2021)
Obesity is a problem that affects not only developing countries, but also middle-income countries. Using anthropometric and socioeconomic information, I analyzed the relationship between obesity and employment and wages in Peru. The results show that an increase in the body mass index (BMI) has a negative relationship with the probability of women working (-0.3 percentage points, on average), particularly among married women. In the case of men, no statistically significant relationship is observed. Regarding monthly wages, an increase in BMI is associated with a 0.8% reduction in women's wages (US$ 2.3, on average).